Kontribusi Kekuatan Power Tungkai dan Keseimbangan dengan Kemampuan Menggiring Bola pada Permainan Sepakbola UPT SD INPRES 4/82 Abbupungeng - Muhammad Basri; Andi Ogo Darminto; Andi Mutmainna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the contribution of leg power and balance to dribbling ability in soccer games among students at UPT SD INPRES 4/82 Abbupuneng. This is a quantitative study with a correlational design. The sample size was 24 students, determined using a proportional sampling technique. Data were collected through leg power, balance, and dribbling ability tests, then analyzed using multiple correlation and F-tests. The analysis results showed a multiple correlation coefficient of R = 0.882 with an F-value of 23.29 (p < 0.05), indicating a significant contribution between leg power and balance to dribbling ability. Thus, leg power and balance play an important role in improving dribbling ability in soccer games.